2014
DOI: 10.1145/2622669
|View full text |Cite
|
Sign up to set email alerts
|

On the Comprehension of Program Comprehension

Abstract: Research in program comprehension has evolved considerably over the past decades. However, only little is known about how developers practice program comprehension in their daily work. This article reports on qualitative and quantitative research to comprehend the strategies, tools, and knowledge used for program comprehension. We observed 28 professional developers, focusing on their comprehension behavior, strategies followed, and tools used. In an online survey with 1,477 respondents, we analyzed the import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
79
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(85 citation statements)
references
References 50 publications
3
79
1
2
Order By: Relevance
“…This is similar to what other research has shown for when programmers read code [1,2,4]. Our participants used a range of strategies to mark specific sections of code (such as highlights and margin bars) and also cross-reference marks to indicate connections between code on different pages.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This is similar to what other research has shown for when programmers read code [1,2,4]. Our participants used a range of strategies to mark specific sections of code (such as highlights and margin bars) and also cross-reference marks to indicate connections between code on different pages.…”
Section: Discussionsupporting
confidence: 70%
“…Therefore the reader may take false routes to find what they need, sometimes even backtracking to revis it previously scanned code [4]. While annotations cannot help find unvisited code they can help reduce the clutter of backwards navigation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent example is a survey on knowledge needs for program comprehension [40], which was implemented using an online survey tool. The survey consisted of 19 fixed-choice questions, and took (according to the authors) "about 15 minutes" to complete.…”
Section: F Sample Surveysmentioning
confidence: 99%
“…These are generally considered as helpful in the process of code comprehension (e.g, as reported by Kosar et al [1] or Storey [3]). However, as Maalej et al observed, many of such IDE tools are left undiscovered even by professional programmers [2], and, similarly to Damevski et al [4], they call for context-aware tools in development environments.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers point out that this process tends to take up to a half of programmers' time during their work with the source code [1,2,3]. The main source of hindrance programmers face during this process lies within the wide semantic gap that is created between the problem domain and the solution domain.…”
Section: Introductionmentioning
confidence: 99%